GREEN COMPETITIVE ADVANTAGE: THE INFLUENCE OF ENVIRONMENTAL AWARENESS AND HUMAN RESOURCES ON SMES - Rafidah, Rafidah; Samad, Khairunnisa Abd.; Adawiyah, Rabiyatul; Rahma, Sri; Alwi, Ahmad Afwan (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This study aimed to thoroughly examine the influence of Environmental Awareness and Green Intellectual Capital (GIC), on Green Competitive Advantage, with Green Human Resource Management (GHRM) serving as the mediating or intervening variable. The investigation is particularly important, specifically considering the fact that business actors are currently paying more attention to the adoption and implementation of green business. This adoption is typically in a bid to address the issue of global warming as well as its impact on nature and the increasing consumer decision to make purchases with consideration for environmentally friendly products. In order to achieve the objective, analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). The results showed that Environmental Awareness significantly influenced the increase of knowledge about the green environment, and this, in turn, impacted the management of competent human resource. Furthermore, intellectual capital (IC) was found to have no direct influence on Competitive Advantage of a business, and Green Human Resource Management acted as an effective mediator of the relationship between Environmental Consciousness affects Competitive Advantage.